Elevated lipopolysaccharide binding protein in Alzheimer’s disease patients with APOE3/E3 but not APOE3/E4 genotype - Romo, Eduardo Z.; Hong, Brian V.; Patel, Rishi Y.; Agus, Joanne K.; Harvey, Danielle J.; Maezawa, Izumi; Jin, Lee-Way; Lebrilla, Carlito B.; Zivkovic, Angela M. (Frontiers in Neurology, 2024)
The role of lipopolysaccharide binding protein (LBP), an inflammation marker of bacterial translocation from the gastrointestinal tract, in Alzheimer's disease (AD) is not clearly understood. In this study the concentrations of LBP were measured in n=79 individuals: 20 apolipoprotein E (APOE)3/E3 carriers with and 20 without AD dementia, and 19 APOE3/E4 carriers with and 20 without AD dementia. LBP was found to be enriched in the 1.21-1.25 g/mL density fraction of plasma, which has previously been shown to be enriched in intestinally derived high-density lipoproteins (HDL). LBP concentrations were measured by ELISA. LBP was significantly increased within the 1.21-1.25 g/mL density fraction of plasma in APOE3/E3 AD patients compared to controls, but not APOE3/E4 patients. LBP was positively correlated with Clinical Dementia Rating (CDR) and exhibited an inverse relationship with Verbal Memory Score (VMS). These results underscore the potential contribution of gut permeability to bacterial toxins, measured as LBP, as an inflammatory mediator in the development of AD, particularly in individuals with the APOE3/E3 genotype, who are genetically at 4-12-fold lower risk of AD than individuals who express APOE4.